New Oscillation Criteria for Third-Order Nonlinear Functional Differential Equations - Quanxin Zhang; Li Gao; Shouhua Liu; Yuanhong Yu (Abstract and Applied Analysis)
This paper discusses oscillatory and asymptotic behavior of solutions of a class of third-order nonlinear functional differential equations. By using the generalized Riccati transformation and the integral averaging technique, three new sufficient conditions which insure that the solution is oscillatory or converges to zero are established. The results obtained essentially generalize and improve the earlier ones.